O modelo de integração econômico e social nas cooperativas agropecuárias do Paraná - Ricken, José Roberto (2009)
The purpose of this study was to analyze the model of integration of agricultural cooperatives in the State of Paraná. There were studied the characteristics, the factors that hinder and the actions that facilitate the integration of cooperatives and their members and of cooperatives between themselves. Cooperatives have distinct characteristics of other market players, in their purposes, form of management, capital formation and identification with the community where they work. The development of rural cooperatives in Paraná is the result of the Integrated Projects of Cooperatives (PICs), implemented as from 1972. The model provided cooperatives at local level, each with its field of action, with the purpose of providing technical assistance, credit and logistical support to groups of associated producers, and central cooperatives by region, for industrialization and commercialization of the production. The results provided by the integrated projects are evident, for almost 60% of the current agricultural production of the State outcomes through cooperatives. However, over time, due to the uneven growth of cooperatives, there appeared disputes about the area of action between cooperatives and conflicts of interests with regard to the central cooperatives, which endangered the idealized model of integration. Field research, conducted in this study concludes that 75% of the people who composes the internal public of’ the cooperatives - members, board members and employees, agree that there is competition between cooperatives in Paraná. This is a controversial but relevant topic for the development of the cooperatives, which compete with large national and international conglomerates. To overcome the dilemma of integration is an important challenge to cooperative organizations. This dissertation uses the methodology of content analysis, described by Vergara (2007, p. 15) to extract from the literature and the field research the desired results. Based on the Theory of Social Systems Delimitation, designed by Guerreiro Ramos (1981), it is concluded that the agricultural cooperatives of the State of Paraná are organizations of economic interests, which show isonomic characteristics of management. The main factors that hinder the integration of cooperatives were assigned to inner attitudes of cooperative members and managers, such as individualism, lack of knowledge about cooperatives and lack of interest in participating in the cooperative. Among the actions that could contribute to the integration was cited the need to form a new model of integration, supported by education, communication programs and capitalization in compatible volumes with the demands of cooperative projects, both for the cooperative members and for integrated projects between cooperatives.